Correction: Germline and reproductive tract effects intensify in male mice with successive generations of estrogenic exposure. - Tegan S Horan; Alyssa Marre; Terry Hassold; Crystal Lawson; Patricia A Hunt (PLoS Genetics, 2017)
[This corrects the article DOI: 10.1371/journal.pgen.1006885.].